Exploring issues of diversity within HBCUs - Ingram, Ted N.; Greenfield, Derek; Carter, Joelle D.; Hilton, Adriel A. (Contemporary perspectives on access, equity, and achievement., 2015)
The purpose of this edited volume is to examine the historical and contemporary dynamics of diversity as well as the realities, challenges, and opportunities associated with diversity work at Historically Black Colleges and Universities (HBCUs). This proposed book will include four sections, focusing on the historical developments and socio-political factors impacting diversity work at HBCUs, organizational structure and philosophical approaches, challenges and opportunities facing particular populations, and analysis of best practices.This text is designed to provide an overview and better understanding of diversity and multiculturalism that exists in historically Black colleges and universities. The contents of the text will examine equity and inclusion efforts in these institutions, and will explore various theories and practices utilized within the academy. Also, the text will examine race, class, gender, ethnicity, nationality, religion, age, ability and sexuality. The goal of the book is to assist students, faculty, and staff in the higher educational landscape in developing their own understandings of historical and contemporary issues related to diversity at HBCUs. Critical analysis of the multiple worldviews will be discussed as we explore the origin, nature and scope of multiple ideologies within diversity, equity and inclusion at HBCUs. In addition, this book will be an invaluable teaching resource for faculty in Educational Leadership Programs, Student Affairs Programs, or Sociology Programs, and other fields interested in issues of retaining and supporting diverse college students.